Semantic Interference and Facilitation: Understanding the Integration of Spatial Distance and Conceptual Similarity During Sentence Reading - Guerra, Ernesto; Knoeferle, Pia (Frontiers in Psychology, 2018)
Existing evidence has shown a processing advantage (or facilitation) when representations derived from a non-linguistic context (spatial proximity depicted by gambling cards moving together) match the semantic content of an ensuing sentence. A match, inspired by conceptual metaphors such as ‘similarity is closeness’ would, for instance, involve cards moving closer together and the sentence relates similarity between abstract concepts such as war and battle. However, other studies have reported a disadvantage (or interference) for congruence between the semantic content of a sentence and representations of spatial distance derived from this sort of non-linguistic context. In the present article, we investigate the cognitive mechanisms underlying the interaction between the representations of spatial distance and sentence processing. In two eye-tracking experiments, we tested the predictions of a mechanism that considers the competition, activation, and decay of visually- and linguistically-derived representations as key aspects in determining the qualitative pattern and time course of that interaction. Critical trials presented two playing cards, each showing a written abstract noun; the cards turned around, obscuring the nouns, and moved either farther apart or closer together. Participants then read a sentence expressing either semantic similarity or difference between these two nouns. When instructed to attend to the nouns on the cards (Experiment 1), participants’ total reading times revealed interference between spatial distance (e.g., closeness) and semantic relations (similarity) as soon as the sentence explicitly conveyed similarity. But when instructed to attend to the cards (Experiment 2), cards approaching (vs. moving apart) elicited first interference (when similarity was implicit) and then facilitation (when similarity was made explicit) during sentence reading. We discuss these findings in the context of a competition mechanism of interference and facilitation effects.